2019
DOI: 10.3892/ijo.2019.4902
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy is a promising therapeutic strategy to overcome chemoresistance and reduce metastasis in osteosarcoma

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy, mainly affecting children and adolescents. Currently, surgical resection combined with adjuvant chemotherapy has been standardized for OS treatment. Despite great advances in chemotherapy for OS, its clinical prognosis remains far from satisfactory; this is due to chemoresistance, which has become a major obstacle to improving OS treatment. Autophagy, a catabolic process through which cells eliminate and recycle their own damaged proteins and organe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 77 publications
1
44
0
Order By: Relevance
“…The elimination and recycling of damaged proteins and organelles are driven by autophagy, which provides energy to the cells. Autophagy can be activated by chemotherapy and can promote increased chemosensitivity, as well as drug resistance in OS (Camuzard et al , 2019; Liao et al , 2019). Thus, drugs regulating autophagy may be an option to overcome drug resistance in the future.…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…The elimination and recycling of damaged proteins and organelles are driven by autophagy, which provides energy to the cells. Autophagy can be activated by chemotherapy and can promote increased chemosensitivity, as well as drug resistance in OS (Camuzard et al , 2019; Liao et al , 2019). Thus, drugs regulating autophagy may be an option to overcome drug resistance in the future.…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Chloroquine and hydroxychloroquine are the only autophagy inhibitors approved by the FDA for clinical use (178), comprehensive reviews are examining the role of various compounds and biological molecules in the regulation of autophagy and various ATG genes (160,176,(179)(180)(181). Clinical trials are underway in which inhibitors of autophagy are administered in combination with chemotherapy or targeted therapy (182,183).…”
Section: Role Of Autophagy In Chemotherapy and Target Therapy Resistancementioning
confidence: 99%
“…Some authors have actually observed that the depletion of autophagy decreased the viability of chronic myeloid leukemia CD34+ progenitor cells, whereas its inhibition in hematopoietic stem cells (HSC) has favored the development of hematopoietic diseases (Auberger and Puissant, 2017;Levine and Kroemer, 2019). On the other hand, after treatment with synthetic or natural compounds, there are some evidences that when the autophagosomal/lysosomal pathway is over activated for a prolonged time the autophagic cell death (ACD, type II cell death) can occur (Liao et al, 2019;Linder and Kögel, 2019). Arsenic trioxide (ATO) has been proved to induce ACD in several cancer cells.…”
Section: Autophagy In Cancermentioning
confidence: 99%